Herpesvirus infections: myths and realities - Makarenko, V (Annals of Mechnikov’s Institute, 2020)
Herpesvirus infections (HVI) is known for more than two millennia, and its main symptoms described by Hippocrates more. But our time HVI remains mysterious and before the end of the unknown. Among the issues are not sufficiently clarified latency of infection and persistence of herpes viruses, the causes of the frequent occurrence of the disease in the form of subclinical forms, high infection rate of the world population, and others. Note that virologists and clinicians are showing in the last 20 years to the HVI, is associated with a variety of ever-increasing role Herpesviridae in infectious pathology of human and social importance of diseases caused by them. It is now known 8 herpesviruses pathogenic for humans. Because of the difference in a number of biological properties, the nature of replication in cell cultures, the clinical picture and the pathogenesis of diseases caused by all herpesviruses are distributed according to the recommendations of the International Committee on Taxonomy of Viruses, in three subfamilies (α, β, γ). Activators of herpes simplex virus can be endogenous and exogenous factors: reduction of immunoreactivity of the organism (immunodeficiency, interferon failure), physical and emotional stress, overheating or overcooling, hormonal disorders, ultraviolet irradiation, corticosteroids treatment, cytotoxic drugs. It is important to understand that the HVI is a disease of the whole body with lesions in varying degrees, all organs and systems (immune, hematopoietic, lymphatic, CNS), which is responsible for the homeostasis of the human body. These data give reason to believe HVI systemic disease, mainly affecting a particular organ. However, more is still not widely used etiopathogenetical and "topical" diagnosis, indicating the loss of any one body. Due to the fact that the clinical forms of HVI are characterized by marked polymorphism, the timely establishment of the etiologic diagnosis is a difficult task and is based on the use of specific molecular genetic, virological, immunological and serological methods. It is generally recognized that the treatment of patients with herpes is quite a challenge for practitioners, it requires professional skills in these patients, a differentiated approach depending on the clinical form of the disease, as well as the condition of the patient’s immune system. Data of own observations have shown that HVI retains its relevance due to the high infection and morbidity in children (more than 30% of all children referred for advice); the need to use complex laboratory studies; the possibility of persistent currents without clinical manifestations and course of active viral replication, requiring the appointment of antiviral drugs. Conclusions. In order to provide quality health care to patients with HVI requires knowledge of modern principles of diagnosis and therapy. Ability to herpesvirus latency and reactivation of the development of manifest forms of the disease necessitates the development of control strategies for the HVI and more efficient use of suppressive antiviral therapy and vaccine prevention.